LEXICOSTATISTICS OF MALAY, TAGALOG AND ILOCANO LANGUAGES: A COMPARISONAL HISTORICAL LINGUISTIC STUDY - Muhammad Kiki Wardana; Dwi Widayati; Rostina Taib; Muhammad Iqbal (Institut Pendidikan Tapanuli Selatan, 2022)
This study tries to explore the relationship between three languages, namely Malay, Tagalog, and Ilocano. The purpose of this study is to find cognates (word relatives), estimate when these three languages ​​are a single language and find the time apart from the three languages. This study uses a language grouping method with a Lexicostatistical approach. The results of this study indicate that Malay and Tagalog share about 28% of words that are related and fall into the category of Stock Clumps. Other results also show that Malay and Ilocano historically and linguistically are closer and classified as category of language stockwith the cognate or related words as much as 31%.